Experimental studies of optoacoustic effect on the model of erythrocytes in the presence of carbon nanoparticles - D. A. Kravchuk; D. V. Orda-Zhigulina (Biomedical Photonics)
Experimental model has been developed to study optoacoustic signal from model blood cells presented by polystyrene microspheres with nanoparticles. It was found out that nanoparticles due to their strong absorption of light significantly affect the coefficient of cellular optical absorption, while the thermophysical parameters, namely the coefficient of thermal expansion, compressibility and isobaric specific heat of cells remain unchanged, since nanoparticles occupy a small intracellular volume compared to the cell volume. Optoacoustic signals were obtained using model solutions at various concentrations of cells and nanoparticles using 1064 nm laser. The results of experimental measurements using LIMO 100–532/1064-U system based on Nd:YAG showed that the amplitude of the optoacoustic signal increased without increasing the temperature in the laser area.